2018
DOI: 10.1002/eji.201847504
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells at the crossroads of microbiota and IBD

Abstract: The human gut harbors a wide range of microorganisms that play a fundamental role in the well-being of their host. A dysregulation of the microbial composition can lead to the development or exacerbation of gastrointestinal (GI) disorders. Emerging evidence supports the hypothesis that mast cells (MCs) play a role in host-microbiota communication, modulating the mutual influence between the host and its microbiota through changes in their activation state. The ability of some bacteria to specifically affect MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 77 publications
0
47
0
1
Order By: Relevance
“…Remarkably, there is increasing evidence describing the role of gut microbiota in the activation of mast cells, in addition to its involvement in amplifying IgE-and non-IgE-mediated allergies. 54,55 Psychiatric comorbidities and psychosocial stress are also common in IBS. However, the exact pathogenesis through which psychological stressors induce symptoms in IBS remains to be elucidated.…”
Section: Mast Cells Play a Significant Role In Maintaining Homeostasismentioning
confidence: 99%
“…Remarkably, there is increasing evidence describing the role of gut microbiota in the activation of mast cells, in addition to its involvement in amplifying IgE-and non-IgE-mediated allergies. 54,55 Psychiatric comorbidities and psychosocial stress are also common in IBS. However, the exact pathogenesis through which psychological stressors induce symptoms in IBS remains to be elucidated.…”
Section: Mast Cells Play a Significant Role In Maintaining Homeostasismentioning
confidence: 99%
“…Accumulating evidences indicated that the function of MCs in IBD is more complicated than originally thought, Animal and human clinical studies suggested that the contribution of these cells includes regulating epithelium permeability, immune signal transmittance, maintenance and resolution of inflammatory responses, and subsequent tissue remodeling [2,[30][31][32][33][34]. What's more, the study showed that the increase of MCs infiltration near the epithelium resulted in a favorable microenvironment that expressed more beneficial proteins including ZO-1, FGF2, ANGPTL2, REG3γ, and REG3β, which are involved in signal transduction, cell growth, tissue repair, and homeostasis maintenance [2].…”
Section: Discussionmentioning
confidence: 99%
“…These cells can be involved in several autoimmune disorders, such as rheumatoid arthritis [37], coeliac disease [94], multiple sclerosis [124], and bullous dermatoses [125]. Mast cell-nerve communications are involved in stress, pain, pruritus [126,127], and in inflammatory bowel diseases [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these cells can be activated by different viral [25,26] and bacterial proteins [27,28] and thereby represent a potentially important cell during microbial infections. Therefore, the spectrum of diseases in which mast cells and their mediators have been implicated has extended to include bacterial, fungal, viral, and helminth infections [26,[29][30][31]; several diseases of the cardiovascular [14,32,33] and gastrointestinal systems [34][35][36]; and the joints [37,38]. Figure 1 schematically summarizes the wide spectrum of pathophysiological conditions in which mast cells and their mediators have been implicated during the last decades.…”
mentioning
confidence: 99%